(untitled) (Journal of Parents and Teachers, 2020)
This article arises from the need to listen and analyse the experience of families during confinement and their expectations with the arrival of the new normality. It is based on the testimony of families with school-age children from Spain, Guatemala and Bolivia and aims to bring those who read it closer to the social and educational reality that has been generated in homes, centres and educational institutions as a result of COVID-19.